The Invariant Moments Based With Wavelet Used To Decide the Authintication and Originality of Images - Hussein, H.L. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The digital image with  the wavelet tools  is increasing nowadays with MATLAB library, by using  this method based on invariant moments which are  a set of seven moments can be derived from the second and third moments , which can be calculated after converting the image from colored map to gray scale , rescale the image to (512 * 512 ) pixel , dividing the image in to four equal pieces (256 * 256 ) for each piece , then for gray scale image  ( 512 * 512 ) and the four pieces (256 * 256  ) calculate  wavelet with moment and invariant moment, then  store  the result with the author ,owner for this image to build data base for the original image to decide the authority of these images by using comparison  using  Mean Square Error (MSE) as shown below :-    MSE=    1010),(),(MyNx ïƒ¥ ï› 1 ï yxfyx N * M  The moments value of any image will be compared with the original data base images moment. The experiments were performed on a Pentium IV, 1.6 GHz processor, running  Microsoft Windows XP and the programs were implemented by MATLAB . Index Termsâ€”  wavelet, digital image, moment